Identifikasi Kesulitan Belajar Siswa dalam Pembelajaran Bahasa Indonesia di Kelas XI MAS Al Jam’iyatul Wasliyah 22 Tembung - Putri, Amalya; Ilmanun, Lulu; Dalimunthe, Winda Vita Puri; Harahap, Robianna; Gajah, Ewin Sanjaya (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to identify students' learning difficulties in learning Indonesian in class XI MAS Al Jam'iyatul Wasliyah 22 Tembung. This research uses a qualitative approach with descriptive methods. The research subjects were class XI students, selected purposively. Data was collected through observation, interviews and documentation studies. The research results show that the learning difficulties experienced by students include four main aspects: (1) listening difficulties (2) speaking difficulties (3) reading difficulties (4) writing difficulties. Factors causing learning difficulties include lack of motivation to learn, minimal mastery of vocabulary, and less varied learning methods. This research recommends using more interactive and contextual learning methods to improve students' understanding of Indonesian language material. In addition, teachers are expected to be able to provide more intensive guidance to overcome students' learning obstacles, so that learning objectives can be achieved optimally.